The Phenomenon of Multiculturalism and the American Cultural Context of the Late 20th Century - Maksudova Mokhigul Usmonovna (International Journal on Integrated Education, 2022)
Multiculturalism is assessed both as an attempt to create a new national "ideology" and "ethics" to replace the shattered ideals of American nationalism, patriotism, democracy, and as a possible way to form a new "national identity", which America is facing today. Particular attention is paid to the rethinking of the heritage of the Enlightenment by multiculturalists in its national version, as well as some positivist doctrines, and, of course, postmodern philosophical and historical concepts, with which supporters of the discourse of diversity argue, but from which they largely repel the future of the literature.